2015
DOI: 10.1051/0004-6361/201425470
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the spatially resolved metal abundance in galaxy clusters up toz= 1.4

Abstract: Context. We present the combined analysis of the metal content of 83 objects in the redshift range 0.09−1.39, and spatially resolved in the three bins (0−0.15, 0.15−0.4, >0.4) R 500 , as obtained with similar analysis using XMM-Newton data in our previous two papers. Aims. By combining these two large data sets, we investigate the relations between abundance, temperature, radial position and redshift holding in the intracluster medium. Methods. We fit functional forms to the combination of the different physic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

29
94
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(127 citation statements)
references
References 29 publications
29
94
4
Order By: Relevance
“…The statistical errors corresponding to D = C 1 with the systematic uncertainties described in Section 4 are added to the total error budget shown in the figure. The ratio of the SN Ia to SN cc is fairly uniform from the core to the outskirts. redshift Perseus and Virgo clusters (Werner et al 2013;Simionescu et al 2015), and the early enrichment timescale is consistent with studies of mass-selected samples of galaxy clusters with redshift < < z 0 1.5 (Ettori et al 2015;McDonald et al 2016). …”
Section: Radial Distribution Of Sn Ia To Sn CC Fractionsupporting
confidence: 86%
“…The statistical errors corresponding to D = C 1 with the systematic uncertainties described in Section 4 are added to the total error budget shown in the figure. The ratio of the SN Ia to SN cc is fairly uniform from the core to the outskirts. redshift Perseus and Virgo clusters (Werner et al 2013;Simionescu et al 2015), and the early enrichment timescale is consistent with studies of mass-selected samples of galaxy clusters with redshift < < z 0 1.5 (Ettori et al 2015;McDonald et al 2016). …”
Section: Radial Distribution Of Sn Ia To Sn CC Fractionsupporting
confidence: 86%
“…While the gas phase metallicities in the outer parts of the cluster are quite similar in both runs, the difference between them (in both the mean value and dispersion) within the core of the cluster (  r 100 kpc) is quite striking. The Cond run reproduces the observational estimates of the metallicity profiles in clusters more faithfully (Leccardi & Molendi 2008, gold shaded region; Ettori et al 2015, solid black curve).…”
Section: Resultssupporting
confidence: 52%
“…This fact is a consequence of the mixing that leads to flattened entropy profiles. Comparison to the observational data of Ettori et al (2015) shows that our simulated clusters have metallicities a factor Á 3 smaller than real cluster both for CCs and NCCs; observations also show that the dichotomy between CCs and NCCs central metallicities is stronger in real clusters than in our simulated sample. In the SPH simulations by Rasia et al (2015) this discrepancy is not observed; its origin in our simulations is unclear, however we are planning to investigate on this issue by performing explicit comparison of AMR and SPH simulations with the same initial conditions and similar sub-grid models in a future paper.…”
Section: Icm Metallicity In Cool Core and Non-cool Core Clusterssupporting
confidence: 49%
“…Figure 9 shows the differential ICM metallicity profile for the R4K simulations at redshift z " 0 when the cluster population is divided in cool core and non-cool core clusters as in Hahn et al (2015). In this figure, the ICM metallicites have been multiplied by a factor 3 to facilitate comparison to the observational results of Ettori et al 2015 (dashed lines; the sample is an extension of the one used by Leccardi & Molendi 2008). Even if the scatter between the haloes (shaded areas) is large it is possible to appreciate how metals are re-distributed differently depending on whether the clusters have a cool core or not.…”
Section: Icm Metallicity In Cool Core and Non-cool Core Clustersmentioning
confidence: 99%
See 1 more Smart Citation